The Effect of Maturity Stage on Polyphenolic Composition, Antioxidant and Anti-Tyrosinase Activities of Ficus rubiginosa Desf. ex Vent. Extracts - Ghaid W. A. Abualzulof; Samir Scandar; Ina Varfaj; Vanessa Dalla Costa; Roccaldo Sardella; Raffaella Filippini; Anna Piovan; Maria Carla Marcotullio (MDPI AG, 2024)
Ficus spp. are often used as food and in traditional medicine, and their biological activities as anti-inflammatory and diuretic, for wound healing, and as antimicrobial agents have been largely reviewed. The aim of this work was to investigate the polyphenol content and the antioxidant and anti-tyrosinase properties of the extracts from F. rubiginosa, a very poorly explored Ficus species. For this purpose, F. rubiginosa leaves were collected at three different maturity stages (H1, H2, and H3), and the environmentally sustainable methanolic extracts were evaluated for the total phenolic content (TPC), total flavonoid content (TFC), and total catechins content (TCC). The polyphenolic profile was studied using HPLC-UV/DAD and UHPLC-MS, and the antioxidant activity was determined in vitro using DPPH, FRAP, and ABTS assays. The study showed that the H2 extract had higher TPC and TFC values (113.50 mg GA/g and 43.27 mg QE/g, respectively) and significant antioxidant activity. Therefore, the H2 extract was selected to study the anti-tyrosinase activity. The results also showed that H2 was able to bind and inhibit tyrosinase, with rutin being the compound responsible for the measured activity on the enzyme.